Vitamin E improves growth of collared flycatcher Ficedula albicollis young: a supplementation experiment. (24th April 2014) - Matrková, Jana; Remeš, Vladimír
<x xml:space="preserve">Abstract</x> In altricial birds, the quantity and quality of food provided by parents is a crucial determinant of nestling performance. Vitamin E is an important micronutrient with various physiological functions, including a positive role in the antioxidant system. Sufficient intake of vitamin E has been shown to condition normal avian development in poultry, yet, our knowledge of the role of vitamin E in free‐living birds is limited. Thus, we experimentally examined the effects of vitamin E on nestling development in the collared flycatcher Ficedula albicollis. We supplemented nestlings with vitamin E and evaluated their growth and survival till fledging. Increased availability of vitamin E did not affect body mass, wing length or survival, but improved tarsus growth. The effect of supplementation on tarsus length changed over season and with initial body mass. Supplemented nestlings that were smaller at hatching and those that hatched later in the season grew longer tarsi compared to the control. Our results suggest that 1) vitamin E may be limiting for the development of collared flycatcher nestlings, 2) seasonal changes of vitamin E availability may affect breeding success of collared flycatchers, and 3) increased income of vitamin E may improve growth of nestlings with bad start in life.